Clinical experience with methylcobalamin (CH3-B12) for male infertility - Isoyama, R (Hinyokika kiyo. Acta urologica Japonica, 1984)
CH3-B12 was administered daily (1,500 micrograms/day, for 4 to 24 weeks) to 26 infertile male patients who visited our clinic from January to December, 1982. It was not administered, however, to patients with azoospermia. Semen analysis was conducted from 8 weeks after the administration of CH3-B12. Sperm concentration increased in 10 cases (38.4%), total sperm counts increased in 14 cases (53.8%), sperm motility increased in 13 cases (50.0%) and total motile sperm count increased in 13 cases (50.0%). Semen volume, however, could not be evaluated due to wide variation. Serum LH, FSH and testosterone were unchanged. Judging by our criteria, 11 cases (42.3%) improved, 11 cases (42.3%) were unchanged and the remaining 4 cases (15.4%) had aggravated